Cell Cycle- and Cancer-Associated Gene Networks Activated by Dsg2: Evidence of Cystatin A Deregulation and a Potential Role in Cell-Cell Adhesion - Gupta, Abhilasha; Nitoiu, Daniela; Brennan-Crispi, Donna; Addya, Sankar; Riobo, Natalia A.; Kelsell, David P.; Mahoney, Mỹ G. (PloS one, 2015)
Cell-cell adhesion is paramount in providing and maintaining multicellular structure and signal transmission between cells. In the skin, disruption to desmosomal regulated intercellular connectivity may lead to disorders of keratinization and hyperproliferative disease including cancer. Recently we showed transgenic mice overexpressing desmoglein 2 (Dsg2) in the epidermis develop hyperplasia. Following microarray and gene network analysis, we demonstrate that Dsg2 caused a profound change in the transcriptome of keratinocytes in vivo and altered a number of genes important in epithelial dysplasia including: calcium-binding proteins (S100A8 and S100A9), members of the cyclin protein family, and the cysteine protease inhibitor cystatin A (CSTA). CSTA is deregulated in several skin cancers, including squamous cell carcinomas (SCC) and loss of function mutations lead to recessive skin fragility disorders. The microarray results were confirmed by qPCR, immunoblotting, and immunohistochemistry. CSTA was detected at high level throughout the newborn mouse epidermis but dramatically decreased with development and was detected predominantly in the differentiated layers. In human keratinocytes, knockdown of Dsg2 by siRNA or shRNA reduced CSTA expression. Furthermore, siRNA knockdown of CSTA resulted in cytoplasmic localization of Dsg2, perturbed cytokeratin 14 staining and reduced levels of desmoplakin in response to mechanical stretching. Both knockdown of either Dsg2 or CSTA induced loss of cell adhesion in a dispase-based assay and the effect was synergistic. Our findings here offer a novel pathway of CSTA regulation involving Dsg2 and a potential crosstalk between Dsg2 and CSTA that modulates cell adhesion. These results further support the recent human genetic findings that loss of function mutations in the CSTA gene result in skin fragility due to impaired cell-cell adhesion: autosomal-recessive exfoliative ichthyosis or acral peeling skin syndrome.